PENGARUH PENGGUNAAN BIOCHAR DAN PUPUK KALIUM TERHADAP PENCUCIAN DAN SERAPAN KALIUM PADA TANAMAN JAGUNG - Widowati Widowati; Asnah Asnah; Sutoyo Sutoyo (BUANA SAINS, 2012)
A glasshouse experiment was conducted to study the effect of biochar and potassium fertilizer on potassium leaching and potassium absorption by maize. A completely randomized block design was used with three replications. There were seven treatments consisting of : Ko : control (no biochar and no KCl), K1: 200 kg KCl, K2 (30 t/ha biochar), K3: (30t/ha biochar + 50 kg/ha KCl), K4: (30t/ha biochar+100 kg KCl), K5:(30 t/ha biochar + 150 kg/ha KCl), K6 : (30 t/ha biochar + 200 kg/ha KCl). The results showed that applications of biochar without potassium fertilizer resulted in leaching, availability and total of potassium soil were high and maximum potassium absorption was 33.95 kg/ha. Potassium absorption from biochar applications did not significantly differ if the treatments were combined with biochar and low application of potassium fertilizer. Application of biochar combinaed with potassium fertilizer did not increased leaching and absorption of potassium by maize